Cytochrome c oxidase subunit I variability in Ruditapes decussatus (Veneridae) from the western Mediterranean. Issue 1 (1st January 2017) - Sanna, D.; Lai, T.; Cossu, P.; Scarpa, F.; Dedola, G. L.; Cristo, B.; Francalacci, P.; Curini-Galletti, M.; Mura, L.; Fois, N.; Maltagliati, F.; Casu, M.
Abstract: Ruditapes decussatus (Linnaeus, 1758) (Veneridae) is an Atlanto-Mediterranean bivalve whose populations have experienced reductions and, in some instances, hybridisation with allochthonous R. philippinarum . Acquisition of additional genetic knowledge concerning the present R. decussatus populations is essential to address adequate conservation plans for this species. For this purpose, we analysed a portion of the mtDNA cytochrome c oxidase subunit I (COI) region in populations from the western Mediterranean, where this species represents a harvested fishery resource. Our analyses revealed an overall lack of genetic structure within the western Mediterranean area, and the occurrence of mtDNA substructuring between the Aegean and Marmara seas and the remaining populations from the whole Mediterranean basin and the South European Atlantic coast. The results obtained for populations from Sardinia, where extensive restocking programmes have not been reported and where R. philippinarum is rare and localised, suggest that intensive harvesting and potential dispersal alone may have been able to shape the genetic variation identified in the local R. decussatus populations.